Treatment of Displaced Lateral Condyle Humerus Fractures in Children by Closed Reduction and Percutaneous Pinning - KC, Kapil Mani; Acharya, Parimal; RC, Dhirgha Raj; Pangeni, Bandhu Ram (Nepal Orthopaedic Association Journal, 2023)
BACKGROUND: Open reduction and internal fixation is the ideal treatment for displaced unstable lateral condyle humerus fractures. Very few studies have focused on closed reduction and percutaneous pinning (CRPP) for displaced lateral condyle humerus fractures in children. We prospectively studied CRPP for displaced lateral condyle fractures (except completely rotated fractures) to evaluate the functional and radiological outcomes.METHODS: We classified the fractures according to the Song et al classification system based on the pattern and displacement of fractures. We included stages II ,III and IV of lateral condyle fractures excluding Stage I and V. Twenty-three patients were finally enrolled in the study. Fractures were reduced under C arm guidance by varus and longitudinal traction and fixed with 2 or 3 parallel K wires. Functional outcomes were evaluated according to the Hardacre et al scores.RESULTS: The average age of patients in our study was 7.91±2.44 years with 15 (65.22%) male and 8 (34. 78%) female patients. There were 13 ( 50.52%) fractures on the left side and 10 ( 43 .48%) on the right side. 9 (39.13%) of fractures were caused by fall from height. Time till union of the fracture was 6.21±1.08 weeks and total duration of hospital stay was 1.65±0.57 days. There were 22 (95.65%) excellent and 1 (4.35%) good results according to the Hardacre et al scores.CONCLUSION: Closed reduction and percutaneous pinning can be tried successfully in minimally displaced unstable as well as displaced unstable lateral condyle fractures with excellent functional outcomes, provided good assessment of pattern and displacement of fractures by internal oblique radiographic views is done.